Efeito protetor da via hemeoxigenase 1/ biliverdina/ CO em modelos de lesões gástricas em camundongos : papel da guanilato ciclase solúvel (GCS) e DA no sintase (NOS) - Gomes, Antoniella Souza (2009)
To evaluate the protective effect of the heme-oxygenase 1 (HO-1)/biliverdin/CO pathway in models of gastropathy in mice, evaluating the role of the soluble guanylate cyclase (GCs) and of the constitutive NOS in this event. Methods: Protocol 1: Mice were pre-treated with hemin (HO-1 inducer; 1,3,10 mg/Kg, i.p.), biliverdin (HO-1 product; 1,3 or 10 mg/Kg., i.p.), DMDC (CO donor; 2.5, 7.5, 12.5 or 10 µmol/Kg, i.p.) or ZnPP IX (HO-1 antagonist; 0,3, 1 or 3 mg/kg. i.p.), one hour before, gastric damage was induced by ethanol 50% (hemin, biliverdin, DMDC) or 25% (ZnPP IX). In another group, the animals were pre-treated with ODQ (12.5 mg/kg, v.o) or L-NAME (3 mg/Kg, v.o), thirty minutes before of the treatments cited previously. After 1h, the mice were sacrificed and the stomachs removed for evaluation of the gastric lesions (Image J). Protocol 2: Mice were pre-treated with hemin (3 mg/Kg, i.p.), biliverdin (3 mg/Kg., i.p.), DMDC (12,5 µmol/Kg) or ZnPP IX (3,0 mg/kg), one hour before of the administration of INDO 30 mg/Kg (hemin, biliverdin, DMDC) or 10 mg/Kg (ZnPP IX). In another group, the animals were pre-treated with ODQ (12.5 mg/kg, v.o) or L-NAME (3 mg/Kg, v.o), thirty minutes before of the treatments cited previously. Three hours after, the mice were sacrificed and the stomachs removed for evaluation of the gastric lesions, utilizing a digital paquimetry. In all of the experimental groups, fragments of the gastric mucous were collected for determination of the concentration of MDA, GSH or bilirubin. Another samples of tissue was removed for microscopic analyzes and HO-1 expression by immunohistochemistry. The detection of the TNF-α, IL-1β, IL-10 and MPO activity were evaluated only in the INDO gastropathy. Results: Ethanol increased the expression of HO-1 and the levels of bilirrubin in the gastric tissue. Hemin, biliverdin and DMDC reduced gastric damage, MDA levels and GSH consume in ethanol 50%- induced gastropathy. The histological parameters, edema, hemorrhage and loses of epithelial cells, were diminished in the presence of hemin, biliverdin or DMDC. ZnPP IX amplified the ethanol-induced gastric lesion, increased MDA formation and decreased the GSH concentration in gastric mucosa. The histological parameters also were amplified after the handling with ZnPP IX. Bilirubin concentration was elevated during the protection induced by hemin and biliverdin, but not DMDC. INDO increased the HO-1 expression and the bilirrubin levels in the gastric mucosa. Hemin, biliverdin or DMDC reduced the gastric lesion, the MPO activity, and the MDA levels and increased the GSH concentration in the gastropathy INDO- induced. The histological parameters, edema, hemorrhage, loss of epithelial cells and the presence of inflammatory cells, were inhibited by hemin, biliverdin or DMDC. ZnPP IX amplified the effect of the INDO increasing the gastric lesion, the MPO activity, the MDA levels and the GSH consume. The histological parameters also were amplified after the handling with ZnPP IX. Bilirubin was shown elevated during the protection induced by hemin and biliverdin, but not DMDC. Hemin, biliverdin and DMDC diminished the TNF-α and IL-1β concentrations and increased the IL-10. ODQ and L-NAME completely abolished the DMDC protective gastric effect, but not biliverdin in the gastropathy ethanol or INDO- induced. Conclusion: HO-1/biliverdin/CO pathway plays a protective effect against ethanol or INDO-induced gastric damage. In the gastropathy by ethanol, the protection is dependent of the anti-oxidant action by bilirubin and CO. However, in the model of INDO gastropathy, we observe an anti-oxidant and anti-inflammatory action. The mechanism of gastro protective action of the CO, but not of the biliverdin, is dependent of the CO/ NOS/ GMPc pathway.